Improving Media Literacy skills in Generation Z in the Digital Era - Diki Riswandi (Sean Institute, 2023)
This research aims to investigate efforts to improve media literacy skills in generation Z. Generation Z, who grew up in the digital era, is exposed to a variety of information and social media that can influence their understanding of news, opinions and other information. This research uses qualitative research methods to analyze the challenges and opportunities faced by generation Z in increasing their media literacy in the digital era. The research results show that Generation Z, who grew up in a tumultuous digital era, has unique characteristics that reflect the impact of technology on their lives. They are very familiar with technology, have the ability to make independent decisions, and show strong ambition in achieving success. However, to increase their media literacy, there needs to be a holistic approach that includes formal education, support from family, and a deep understanding of digital media. Steps such as media education in schools, critical learning, developing research skills, awareness of media bias, positive use of social media, critique of digital content, and supporting creativity are important elements in helping Generation Z become wise media consumers, critical, and contribute positively in a digital society that continues to develop. This discovery makes an important contribution in supporting the development of generation Z media literacy, which is a key aspect in facing the challenges and opportunities in today's digital era.